Electronic structure modulation of isolated Co-N4 electrocatalyst by sulfur for improved pH-universal hydrogen evolution reaction. (February 2021) - Sabhapathy, Palani; Shown, Indrajit; Sabbah, Amr; Raghunath, Putikam; Chen, Jeng-Lung; Chen, Wei-Fu; Lin, Ming-Chang; Chen, Kuei-Hsien; Chen, Li-Chyong
Abstract: Exploring an efficient platinum group metal (PGM) free electrocatalyst with superior activity and stability for hydrogen evolution reaction (HER) in a wide pH range is desirable for low-cost hydrogen production. Here, we report atomically dispersed cobalt on nitrogen and sulfur co-doped graphene (N-Co-S/G) for HER. Remarkably, the prepared N-Co-S/G electrocatalyst shows a small overpotential of 67.7 mV vs. reversible hydrogen electrode (RHE) at a current density of 10 mA cm −2 and exceptional durability over 100 h at 10 mA cm −2 under acidic conditions. Moreover, we found that the HER activity of N-Co-S/G is close to 20% Pt/C at all pH levels (0–14) and superior activity at high current density (>100 mA cm −2 ). Experimental and theoretical calculations reveal that the S atom in N-Co-S/G form Co-S bond, resulting new Co-N3S1 active site, which optimizes Gibbs free energy for hydrogen adsorption (∆GH *) close to zero, while water adsorption and dissociation enhanced by S modulation for neutral and basic media HER. Graphical Abstract: An electronic structure modulation was demonstrated to boost the electrochemical HER process over Co-N3S1 (called N-Co-S/G) from a two-step solid-state pyrolysis process. The N-Co-S/G electrocatalyst shows not only excellent activity and stability in acidic solution but also outperform commercial Pt/C in all pH values and seawater at high current density. ga1 Highlights: An electronic structure modulation for accelerating the HER process was demonstrated. The unique new Co-N3S1 system (called N-Co-S/G) was synthesized by two-step solid-state approach was established. The HER activity of N-Co-S/G can be promoted and maintained. The N-Co-S/G can be used in all pH and seawater hydrogen production. The sulfur modulation eventually boosts the HER kinetics and water adsorption and activation step.